“I Am Not Just a Prisoner”: the effects of social identification on well-being in Italy - Cristina O. Mosso; Alessandra Caldera; Camilla Re (Frontiers in Psychology)
Recent research on social cures has posited that one’s social identity associated with group membership can promote adjustment and affect well-being, especially for vulnerable individuals. In this study, we argue that, although the negative consequences of group-based stigma affect prisoners’ well-being, having multiple social identities can protect them and mitigate the detrimental effects of stigma. The results of this cross-sectional study reveal that group identification with prisoners (N = 52) was negatively associated with well-being and anticipated discrimination. In contrast, education was positively associated with self-regulation and life satisfaction. Group identification with prisoners threatens self-regulation when the salience is controlled. We discuss the significance of our findings in the context of stigma and resocialization.